Control system of the sun refl ection for central receiver system - Janthong, Manusak; Praditapai, Atirat (Asia-Pacific Journal of Science and Technology, 2017)
This paper presents a control system of the sun refl ection for a central receiver system which consists of 2 subsystems: the sun tracking system and sunlight refl ecting system. The structure of the sun tracking system has 2 DOF and an industrial camera was used to detect the sun position. The sunlight refl ecting system has 2 DOF and a mirror was installed at the top of the structure to refl ect the sunlight. PID controller was implemented to control the sun tracking system and to regulate the center of sun position at the center of image data. Then the sun position was calculated to control the rotation of the sunlight refl ecting system in order to refl ect the sunlight to the target. The experiments can be divided into 3 parts. Firstly, to test the system response and the accuracy of the tracking by using the electric bulb as the sun. It was found that 0.5 s peak time, 1.5 s settling time and ±3 pixel of steady state error could be achieved. Secondly, to test the sun tracking system, it was shown that the system worked well and had error within ±5 pixel. Finally, to test the working performance between the tracking system and the sunlight refl ecting system, it was seen that the system worked well and had error within ±0.5 meters.